The Expected Value of Richard Distribution - Demirelli, Arzu Ekinci (Amer Inst Physics, 2017)
The Richard distribution within the known flexible distribution comes within the distributions providing the best fit to the data. This study focussed on the calculation of the expected value by taking the Richard distribution into consideration. A form is examined which will facilitate the numerical calculation and give the expected value.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 19-25, 2016 -- Rhodes, GREECE